Idiolect and common language - Petrenko, Anton (University of Ottawa (Canada), 2006)
This dissertation concerns the debate on the priority of idiolect over common language. In the course of this work Michael Dummett's argument for the priority of common language will be elucidated and some of the misunderstandings that have pervaded the debate will be identified. A number of ways to deflate the disagreement between Dummett's position and various philosophical approaches he criticizes will be suggested where possible. One of the main goals of this work will be to assess the strength and the fairness of Dummett's argument as it relates to the work of Quine. It will be argued that given a certain reading of Quine's thesis of indeterminacy of translation Dummett's argument may apply to it, but ultimately remains ineffective. It will be argued that an alternative argument, based on Kripke's reading of Wittgenstein, would be more effective against the idiolect conception of language.
Keywords: Philosophy.; Language, General.